Evaluating the Impact of Board Effectiveness and Audit Committee Performance on Audit Quality during the Covid-19 Pandemic: Evidence from Indonesian Firms - Prihantini, Febrina Nafasati; Januarti, Indira; Darsono, Darsono (International Journal of Economics and Financial Issues, 2025)
Audit is the main foundation of the corporate governance system. However, the level of audit efficiency is highly dependent on the actual conditions and changes in the corporate governance environment. This is because effective corporate governance tends to produce accurate and reliable financial reports, while poor governance is often followed by corporate scandal practices and fraudulent actions. The purpose of this study is to evaluate the effect of the effectiveness of the board of commissioners and audit committee during the COVID-19 pandemic on audit quality, especially in the context of providing going concern opinions and the size of the accounting firm. The sample used consisted of 112 Indonesian companies listed on the IDX during the 2019-2022 period. The logistic regression method was used in this study for the data analysis process. The results show that the effectiveness of the board of commissioners and audit committee does not have a significant correlation with the provision of going concern opinions. This opinion better reflects the direct responsibility of the auditor and the results of the audit process carried out by the auditor, and directly shows the independence of an auditor. The effectiveness of the board of commissioners and audit committee influences the determination of the size of the accounting firm, this is due to the role and function of the board of commissioners and audit committee in managing corporate governance.